THEORETICAL FUNDAMENTALS OF CARIES PREVENTION - Axmedova Malika Qilichovna (Journal of Science in Medicine and Life, 2024)
The majority of the world's population suffers from dental caries. According to estimates, 90% of people on earth are infected with this disease. Dental caries remains one of the main global health problems. This disease itself is a simple black point. when it begins, it leads to the loss of the tooth in our mouth. The purpose of prevention is not to fight the disease, but to prevent it from appearing.